The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3945/ajcn.110.001669
|View full text |Cite
|
Sign up to set email alerts
|

The OBELIX project: early life exposure to endocrine disruptors and obesity

Abstract: The hypothesis of whether early life exposure (both pre- and early postnatal) to endocrine-disrupting chemicals (EDCs) may be a risk factor for obesity and related metabolic diseases later in life will be tested in the European research project OBELIX (OBesogenic Endocrine disrupting chemicals: LInking prenatal eXposure to the development of obesity later in life). OBELIX is a 4-y project that started in May 2009 and which has the following 5 main objectives: 1) to assess early life exposure in humans to major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…During this period of life, and more specifically during embryonic gonadal sex determination, chemicals can exert effects at very low levels of exposure and may involve epigenetic events that could be transgenerationally transmitted (Anway et al, 2005). Hence, some research projects are studying the effects of these chemicals on obesity development, such as OBELIX (Legler et al, 2011), and will include epigenetic analyses in both animal models and children.…”
Section: Endocrine Disruptors and Toxicsmentioning
confidence: 99%
“…During this period of life, and more specifically during embryonic gonadal sex determination, chemicals can exert effects at very low levels of exposure and may involve epigenetic events that could be transgenerationally transmitted (Anway et al, 2005). Hence, some research projects are studying the effects of these chemicals on obesity development, such as OBELIX (Legler et al, 2011), and will include epigenetic analyses in both animal models and children.…”
Section: Endocrine Disruptors and Toxicsmentioning
confidence: 99%
“…boys were more susceptible than girls to growth restrictions [26]; (b) poor neurodevelopment, in which the results indicated an association of PCBs with decreased Mental Development Index (MDI), and reduced levels of thyroid hormone [27, 28]; hearing impairments, wherein the results showed that PCB exposures were associated with harmful effects on the outer hair cells of the cochlea [29]; endocrine disruption, characterized by an increase in the prevalence of several subclinical and overt thyroid and metabolic disorders [30, 112]; and diabetes, showing that increasing serum concentrations of individual POPs considerably increased the prevalence of pre-diabetics indicators [10]. …”
Section: Pcbs Exposures In Human and Early Disease Biomarkers: A Genomentioning
confidence: 99%
“…To test this, we challenged primary PBMC with five different endocrine disrupting chemicals (EDCs) and studied their gene expression response in vitro. The chemicals used in this experiment (PCB126, PCB153, BDE47, PFOA, and BPA) were chosen from major classes of EDCs that can be found as food contaminants (Legler et al, 2011). This study was set up as a screening experiment to find compound-specific gene expression profiles and search for obesity-related gene expression changes.…”
Section: Discussionmentioning
confidence: 99%